The effect of physic conditions of Caliandra calothyrsus and its mixing with fresh Gliricidia sepium toward the consumption and nutrient digestibility of sheep - ., Firdus; Astuti, Dewi Apri; Wina, Elizabeth (Indonesian Animal Sciences Society, 2004)
It is reported that feedstuff preparation affects intake and digestibility of the ration. The objective of this experiment was to know the effect of physic conditions of Caliandra calothyrsus and its mixing with fresh Gliricidia sepium toward the digestibility and nutrient consumption of sheep. Fourty nine (49) thin tail sheep with the average body weight of 15.42 kg (SD 2.68) was randomly assigned into one out of five treatment groups of greenery feed which composed of different fresh Penisetum sp. (FP), fresh Caliandra calothyrsus (FC), fresh Gliricidia sepium (FG), dried C. calothyrsus (DC) and steamed C calothyrsus (SC). Treatment A (70% FP + 30% FC), B (70% FP + 30% FG), C (70% FP + 15% SC + 15% FG), D (70% FP + 15% DC +15% FG) and E (70% FP + 15% DC + 15% FG). The treatments had been carried out for 90 days. Water was given ad libitum. Parameters recorded in this experiment were nutrient consumption (dry matter/BK, crude protein, energy) and nutrient digestibility (BK, crude protein, energy). Data recorded were processed by covariant analysis with body weight of sheep at the early experiment treatment as a covariant. Results of the experiment showed that there were significant difference (P<0.05) between fresh, dried, and steamed C. calothyrsus and its mixing with fresh G. sepium toward the consumption and nutrient digestibility. The average of consumption and nutrient digestibility value were high in mixing treatment of 15% fresh C. calothyrsus with 15% fresh G. sepium. Â Key words: Sheep, Caliandra calothyrsus, Gliricidia sepium, consumption, digestibility